Pelatihan Penggunaan Google Form Sebagai Media Untuk Pengumpulan Data Bagi Anggota Pemberdayaan Kesejahteraan Keluarga (PKK) Desa Gedongmulyo Kecamatan Lasem Kabupaten Rembang - Endang Larasati Setianingsih; Sri Suwitri; Ida Hayu Dwimawanti; Juang Abdi Muhammad; Satria Aji Imawan; Renata Jati Nirmala; Asih Widi Lestari; Mochamad Rizki Fitranto (WINDRADI: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aimed to enhance the digital capacity of members of the Family Welfare Empowerment (PKK) group in Gedongmulyo Village, Lasem Subdistrict, Rembang Regency, particularly in utilizing Google Forms as a tool for data collection. In today’s digital era, proficiency in information technology has become essential, including for community-based organizations at the village level. The training was designed to provide participants with practical and applicable knowledge on how to create, distribute, and manage data through Google Forms. The training methods included lectures, demonstrations, and hands-on practice using a participatory approach to ensure effective knowledge transfer. The results of the activity showed a significant improvement in participants' understanding and skills. They successfully developed various digital forms tailored to organizational needs, such as family health surveys, attendance records, and activity evaluations. Beyond improving efficiency in data collection, which was previously done manually, this activity also contributed to enhancing the digital literacy of village residents. The training is expected to serve as an initial step toward digitalizing the administrative functions of the Gedongmulyo PKK and to inspire similar technology-based innovations within other grassroots community organizations.